Rapid detection and quantification of Neoparamoeba perurans in the marine environment - Bridle, AR; Crosbie, PBB; Cadoret, K; Nowak, BF (Aquaculture, 2010)
The protozoan parasite Neoparamoeba perurans is the causative agent of amoebic gill disease (AGD) and an emerging threat to the aquaculture of marine finfish species worldwide. Despite several years of research and continuing efforts the culture of N. perurans remains elusive. As a result current detection methods rely on molecular techniques namely, polymerase chain reaction (PCR) and in situ hybridization (ISH). In this study, a total DNA extraction technique combined with a highly sensitive real-time PCR assay using primers specific for N. perurans was developed and validated. Using this method we were able to detect a single 18S rRNA gene copy and readily detected N. perurans with the lowest detection limit for N. perurans cells spiked in sea water being one cell (100% detection rate). The genome of N. perurans contains multiple copies of the 18S rRNA gene, and an estimate of 2880 copies per cell was derived from real-time PCR calibration curves for cell suspensions and plasmid DNA. The developed method was applied to seawater samples collected from both an experimental AGD infection tank and a variety of environmental sites including those used to culture Atlantic salmon (Salmo salar L.) in Tasmania, Australia. Detectable populations were highly abundant from sites in and closely surrounding cage culture of Atlantic salmon. Furthermore, the method when applied to gill swabs from an on-farm gill pathology assessment demonstrated that non-destructive semi-quantitative analysis of amoebae loads from these fish was possible. Not only does this study provide evidence that N. perurans is a free-living amoeba but the quantitative nature of this novel assay clearly demonstrates the impact of marine cage aquaculture on the prevalence of this fish pathogen and is a step towards establishing the distribution of N. perurans in the marine environment and its relationship with AGD outbreaks. 2010 Elsevier B.V.